Dreaming and Building Another Education: Characteristics of the Progressive Curriculum and Pedagogical Proposal in Costa Rica in the Second Half of the Twentieth Century and Beggining of the XXI Century - Toruño Arguedas, César (2022)
This essay is the first of a triad of academic publications titled "Dreaming and building another education" oriented to the curricular and pedagogical analysis of proposals. To make these publications, alternative education proposals were analyzed during the period under study through publications and interviews with participants in the formulation of these selected educational alternatives. The methodology was supported by secondary documentary sources and semi-structured interviews. The information collected was analyzed through a content analysis; which allowed to establish the characteristics of the alternative curriculum built from this pedagogical movement. The study concludes the existence of structuring elements of the progressive curriculum and pedagogical proposal in Costa Rica at the end of the twentieth and early 21st centuries.